Elizabethan naval administration - Knighton, C. S.; Loades, D. M. (Publications of the Navy Records Society., 2013)
This is the first general selection from the substantial body of surviving documents about Elizabeth's navy. It stands alongside The Navy of Edward VI and Mary I with which it shares much common apparatus and complements the other NRS volumes that deal specifically with the Spanish Armada. This collection concentrates (though not exclusively so) on the early years of Elizabeth's reign when there was no formal war. The documents selected emphasize the financial and administrative processes that supported these operations, such as mustering, victualing, demobilisation, and ship maintenance and r.